Changing community health service delivery in economically less-developed rural areas in China: impact on service use and satisfaction. Issue 2 (28th February 2014) - Liu, Yong; Yuan, Zhaokang; Liu, Yuxi; Jayasinghe, Upali W; Harris, Mark F
Abstract : Objective: To evaluate the impact of a model of rural community health service (CHS) on the use and acceptability of primary healthcare services. Design: Quasi-experimental. Setting: Two adjacent rural counties in China. Participants: 5842 residents in 2009 and 3807 in 2010 from 980 households in 7 intervention townships and 49 villages; 2232 residents in 2009 and 2315 in 2010 from 628 households in 3 comparison townships and 9 villages. All residents were approached to participate, with no significant differences in age or sex between groups. Intervention: Multilevel intervention in 2009 including training rural practitioners, encouraging clinic improvements, providing clinical guidelines, standards and subsidies. Data collection: Surveys of community members from randomly sampled households in 2009 and 2010. Primary outcome measures: Satisfaction with and utilisation of outpatient and public health services. Analysis: Factor analysis confirmed two components of satisfaction. Univariate and multilevel analysis was used. Results: Satisfaction scores for intervention county respondents increased from 21.4 (95% CI 21.1 to 21.7) to 22.1 (95% CI 21.7 to 22.4) with no change in comparison area. In multilevel analysis, satisfaction with patient-centred care was associated with chronic disease, shorter waiting times and county. Satisfaction with clinic environment and cost was associated with female gender, shorter waiting times but not county. The proportion of children receiving immunisation in intervention village clinics increased from 42.5% (95% CI 27.9% to 47.1%) to 59.2% (95% CI 53.8% to 64.6%) whereas this decreased in comparison villages (16.5%; 95% CI 10.3% to 22.7% to 6.0%; 95% CI 1.3% to 10.7%). Antenatal visits increased in intervention villages (from 69.0%, 95% CI 65.8% to 73.1% to 75.8%, 95% CI 72.2% to 79.4%) with no change in comparison villages. Conclusions: Introduction of a CHS model adapted to economically less-developed rural areas was associated with some improvements in satisfaction with care and use of some village-based public health services. Further research is needed to determine its public health impact and application to other areas.